Research of fracture of doped titanium alloys under cavitation - Коваленко, Владимир Иванович; Маринин, Владимир Григорьевич (Eastern-European Journal of Enterprise Technologies, 2015)
The paper presents experimental results on the measurement of the fracture value under the influence of cavitation on titanium alloys doped with Al, V, Mo and Ti-Al coatings. The coatings were formed of erosion vacuum-arc discharge plasma at simultaneous operation - Al and Ti cathodes mounted at an angle of 90о with respect to each other. The substrate, on which the coating was deposited, is at an angle of 45о to both cathodes. To create a cavitation zone, in which samples were established, ultrasonic vibration transducer of the exponential profile was used. The vibration frequency of the end surface of the transducer is equal to 20 kHz, amplitude - 302 microns. Measurements of the fracture value were carried out by the gravimetric method with an accuracy of 0.015 mg. The kinetic curves of fracture of the samples were obtained. The dependence of the average failure rate of titanium alloys on the surface vibration amplitude of the transducer, creating a cavitation zone in the form of a ratio , where B, are constants for a given material was established. The dependence of on the value of microhardness (Н) of the alloy is described by analytical relationship , where a = 28.4, n=–2.9, H is measured in GPa. The possibility of increasing the cavitation resistance of alloys more than twofold by drawing the Ti-Al coatings on their surface was shown.